A constituição das interações em sala de aula e o uso do livro didático: análise de uma prática de letramento no primeiro ciclo - Maria do Socorro Alencar Nunes-Macedo; Eduardo Mortimer Fleury; Judith Green (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
The article discusses aspects of school literacy in a first cycle classroom, in which the use of the didactic book is central. For that purpose, thirty seven hours have been videotaped. The analysis has focused on the interaction processes undertaken by the teacher and the pupils, around the didactic Portuguese book. It has been observed that the teacher changes the initial proposal of the book and gives it new meanings according to her own practice. The analysis built on the concepts of Bakhtin theory and of interactions ethnography about the constitution of literacy processes. Based on the discoursive aspects of the interactions, it particularly evidenced that classroom discourse has different meanings to different participants. It has shown that pupils and the teacher have undertaken social roles that mark an asymmetrical relation in the teaching and learning process.